Bezpieczeństwo ekonomiczne państwa w procesie globalizacji gospodarki - Jeliński, Bohdan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Economic security is understood as a way of expressing society needs in an economic sphere. Besides "political" and "military" it is one of the three pillars of public security. The importance of the economic pillar in modern economy increases systematically because of globalization. Globalization can be characterized as a trend towards greater integration and independence between countries and regions of the globe. It directly means that national economy is more open for international influences, in positive and negative aspects. It is a fact, that these days it is impossible to imagine effective development of the national economy without international co-operation. The method to control relations between national and international economies from national interest point of view is country international policy. The quality of this policy could increase national economic security. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 160-174